Metaphor to Métier: Kerry Tribe’s “Aphasia Poetry Club” and the Discourse of Disability in Contemporary Art - Leslie Cozzi (Arts, 2020)
“Metaphor to Métier: Kerry Tribe’s Aphasia Poetry Club and the Discourse of Disability in Contemporary Art” explores a 2015 video work by Los Angeles-based artist Kerry Tribe. Tribe’s “The Aphasia Poetry Club” embodies a shift in contemporary artistic discourse around concepts of physical and cognitive disability. Created by a neurotypical artist, the work uses the medium of the moving image to interpret the experience of aphasia, a neurocognitive language disorder frequently associated with traumatic brain injury. Three distinct visual idioms capture the particular neurological profiles and linguistic patterns of Tribe’s chosen participants. Tribe’s representation of people living with aphasia disrupts ableist conceits about the human capacity for memory and language. Rather than stigmatizing individual impairments, the work is indicative of a new aesthetic arising from disability experience. The article argues that disability no longer functions in the contemporary art world as a political or spiritual metaphor, but rather has become a site of formal invention and conceptual research.